2012 IEEE International Reliability Physics Symposium (IRPS) 2012
DOI: 10.1109/irps.2012.6241881
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical correlation between current-collapse and fe-doping profiles in GaN HEMTs

Abstract: In this work, for the first time, the dependence of the GaN HEMTs current collapse from the profile of the Fe-doped semi-insulating GaN buffers has been demonstrated both experimentally and by means of numerical simulations based on the SIMS measured profile of the GaN buffer Fe-doping concentration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Similar results have been reported in several research works on deep-level transient spectroscopy in (Al)GaN layers [6] [7] [8] [9]. Different research works reported that the irondoping may be the cause for enhanced currentdispersion effects [10] [11] [12]. Consistently with our results, enhanced dispersion-effects are ascribed to enhanced density of the deep-trap-level E C -0.56 eV / 10 -15 cm 2 , labelled in this work as E2.…”
Section: Pulsed I-v and Drain Current Transient Spectroscopysupporting
confidence: 89%
“…Similar results have been reported in several research works on deep-level transient spectroscopy in (Al)GaN layers [6] [7] [8] [9]. Different research works reported that the irondoping may be the cause for enhanced currentdispersion effects [10] [11] [12]. Consistently with our results, enhanced dispersion-effects are ascribed to enhanced density of the deep-trap-level E C -0.56 eV / 10 -15 cm 2 , labelled in this work as E2.…”
Section: Pulsed I-v and Drain Current Transient Spectroscopysupporting
confidence: 89%
“…DCTs can be recorded with a sensing condition lying in the linear [368], [484], [485] or in the saturation region [390], [486], [487]. Significantly different results might be obtained when comparing results obtained in the linear and saturation region [481].…”
Section: Bias Conditionsmentioning
confidence: 99%
“…Secondary ion mass spectrometry (SIMS) measurements were undertaken on similar wafers [shown in Fig. 3(b)] [10], [11]. Both wafers incorporated a conventional Fe doping profile in the GaN bulk to suppress short-channel effects, having a peak density of 3 × 10 18 cm −3 , which decreased exponentially towards the surface.…”
Section: Device Under Test and Measurementsmentioning
confidence: 99%